Towards Earlier and Improved Detection of Oropharyngeal Swallowing Disorders in the Acute Care Setting - Farrell, Zelda Maria (Trinity College Dublin. Department of Linguistic, Speech and Communication Sciences, 1999)
Oropharyngeal swallowing disorders (OPSD) leading to aspiration and reduced swallow efficiency are common in the acute care setting. Patients presenting with swallow disorders are at a significant risk of developing medical complications such as pneumonia, malnutrition, dehydration and weight loss. Such complications are known to contribute significantly to patient morbidity and mortality. If swallow disorders are detected early there are many different strategies which can be used to treat the problem effectively and minimise, or in many cases, eliminate the aspiration and improve overall swallow efficiency. This allows the patient to eat a regular diet safely.
Keywords: dysphagia